The Influence of Damage to the Geomembrane Layer on the Seepage Pattern and Discharge at the Homogeneous Embankment Dam - Wijayanto, Achsin; Juwono, Pitojo Tri; Cahya, Evi Nur (Civil and Environmental Science Journal (CIVENSE), 2021)
Placing the geomembrane layer on the upstream slope can control the seepage in homogeneous dams. Poor geomembrane design, construction and maintenance caused damage to the geomembrane that caused a leak through the dam body. This study discusses the effect of damage on the geomembrane layer at the homogeneous embankment dam on the seepage pattern and discharge. The study location is in the Sianjo Anjo dam, Aceh Singkil district, a homogeneous dam with a geomembrane layer located in the dam body's upstream part. The damage of the geomembrane layer is assumed caused by the various defect of locations and size. The results show that the seepage pattern (phreatic line) tends to be weak in the geomembrane layer without damage.Â  Meanwhile, if the geomembrane layer is damaged, the larger the defects' width, the higher the phreatic line. However, the seepage pattern that occurs shows insignificant or almost the same. The seepage discharge increases with increasing defect width and decreasing defect location.